ANALISIS KESULITAN BELAJAR SISWA DITINJAU DARI GAYA BELAJAR PADA MATA PELAJARAN IPS DI SMP DARUL LUGHAH WAL KAROMAH - Anjana, Fika; Bahrudin, Babul (Universitas Negeri Makassar, 2024)
This research aims to analyze students' learning difficulties in terms of learning styles in social studies subjects at Darul Lughah Wal Karomah. Descriptive qualitative is used to determine the paradigm of this research. Interview, observation and documentation are the methods used in this research to collect data. The results of this study explain that: The visual learning style dominates among other learning styles with a percentage of 56.6%, and it is followed by the kinesthetic learning style at 33.3%, and the auditory learning style at 10%. The visual learning style can be seen in students with concrete evidence that must be shown firstly so it can make students understand in lesson. The characteristics of students who have a visual learning style are a high need to see and capture information visually before they understand it. The auditory learning style can be seen from students who are able to become fluent speakers, like to discuss things and explain things at length. Students with this type of learning style are easily distracted by noise and are weak in visual activities. The kinesthetic learning style can be seen in students who find it difficult to sit still for hours because of their desire for activity and exploration.